2006
DOI: 10.1002/pssa.200566186
|View full text |Cite
|
Sign up to set email alerts
|

Non‐linear effects in the quenching of fluorescent semiconductor nanoparticles by paramagnetic species

Abstract: Quenching of quantum dot luminescence by nitroxides shows steep exponential behavior and is dependent on nanoparticle size, being most effective for the smaller particles. The interaction of CdSe nanoparticles with TEMPO (non‐binding) and 4‐amino‐TEMPO (binding) has been examined using fluorescence and electron spin resonance techniques. The data suggest that quenching involves an electron exchange mechanism. (© 2006 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 17 publications
8
65
1
Order By: Relevance
“…The results indicated that pure QDs could be easily quenched by the free radicals produced from K 2 S 2 O 8 , which was commonly used to initiate radical polymerization in aqueous and emulsion media. Similar results were also observed by some researchers in the TEMPO-initiating system [39,40]. The structure of the assembly could protect the inside QDs from free radical quenching, though the reasons for the fluorescent recovery were not clear.…”
Section: Properties Of Qds/peg-b-pdmaema Nanocomposite Assembliessupporting
confidence: 87%
“…The results indicated that pure QDs could be easily quenched by the free radicals produced from K 2 S 2 O 8 , which was commonly used to initiate radical polymerization in aqueous and emulsion media. Similar results were also observed by some researchers in the TEMPO-initiating system [39,40]. The structure of the assembly could protect the inside QDs from free radical quenching, though the reasons for the fluorescent recovery were not clear.…”
Section: Properties Of Qds/peg-b-pdmaema Nanocomposite Assembliessupporting
confidence: 87%
“…[11][12][13]24,25 Here, assuming the size-dependent quenching effects of QDs by Hg 2+ could be attributed to the above reasons, then, it is inconsistent to interpret why Cu 2+ quenches larger particles more efficiently. Previously, Chen et al 5 reported that 3.0 nm L-cysteine-capped CdS QDs showed a selective response to Zn 2+ , but a minimal response to Cu 2+ , while the fluorescence of 3.5 nm thioglycerol-and 5.0 nm polyphosphate-capped CdS QDs was remarkably quenched by Cu 2+ .…”
Section: mentioning
confidence: 91%
“…In addition, it was noted that the quenching efficiency reduced with the particle size increase from QDs-3 to QDs-4. It is well known that larger particles possess smaller quenching radius than smaller ones according to the model recommended by Scaiano et al [35,36]. When the particle size reaches to the certain extent, the dimension may become a major factor affecting quenching efficiency.…”
Section: Article In Pressmentioning
confidence: 99%